2020
DOI: 10.1177/1120700020950247
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive analgesia in hip arthroscopy: intra-articular bupivacaine does not improve pain control after preoperative peri-acetabular blockade

Abstract: Introduction: Literature addressing postoperative pain management after hip arthroscopy is relatively scarce. This study aimed to assess if there was added analgesic benefit associated with postoperative intra-articular bupivacaine blockade for patients who received preoperative peri-acetabular blockade for hip arthroscopy procedures. Methods: 52 patients were included in this comparative cohort study. Group 1 consisted of 20 patients who received preoperative peri-acetabular blockade and postoperative intra-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Preemptive analgesia is an important part of multimodal analgesia, which means that various analgesic measures are adopted in advance to inhibit the sensitization of peripheral and central pain nerves. It can improve the pain threshold of patients and reduce the degree of pain experienced [ 7 ]. Many studies have demonstrated the positive effectiveness of preemptive analgesia in TKA [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preemptive analgesia is an important part of multimodal analgesia, which means that various analgesic measures are adopted in advance to inhibit the sensitization of peripheral and central pain nerves. It can improve the pain threshold of patients and reduce the degree of pain experienced [ 7 ]. Many studies have demonstrated the positive effectiveness of preemptive analgesia in TKA [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%